Perancangan Fasilitas Wisata di Teluk Lampung menggunakan Metode Poetic Architecture - Shofia Islamia Ishar; M.Shubhi Yuda Wibawa (Inovasi Pembangunan : Jurnal Kelitbangan, 2017)
Poetic Archtitecture was the most effective methods to design tourism facilities in Lampung Bay. Besides as a methods having the ability to enrich creativity, Poetic Architecture could also direct architects to be more sensitive to treat nature in their designing process. The aim of applying this methods was to explore natural potentials in Lampung Bay and to invite people to appreciate nature that had been abandoned. Poetic Architecture Methods in the research was applied into the design of tourism facilities such as seats and pedestrian track. There were several steps in applying this method which were to conserve natural elements by minimizing human interventions, to literally interpret nature elements as the main design concept and to apply materials whichwould give poetics ambience